Evaluation of a braille-based colour code proposal for people with visual impairment (Human Factors in Design, 2021)
People with visual impairment (PVI) are a group that have some sort of visual loss, including individuals with low vision and blindness. As colour is one of the most important elements in transmitting visual information, its lack of access can be configured as an information and communication barrier, which impacts daily routines and social inclusion. The present study evaluates the suitability of a braille-based colour code proposal for PVI called Universal Colour Code (UCC). Based on user experience methods, exploratory interviews, free association of words, effectiveness tests, and assessment of code were conducted. The results show that UCC has potential for PVI who master braille.
Keywords: Colours; Braille; Qualitative research; People with visual impairment; User experience